2004
DOI: 10.1113/jphysiol.2003.054825
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the alterations of Na+,K+‐ATPase following ischaemia–reperfusion injury in the rat kidney

Abstract: Postischaemic acute renal failure (ARF) is influenced by sex. Na + ,K + -ATPase (NKA) plays a crucial role in the pathogenesis of postischaemic ARF. We tested the impact of sex on mRNA, protein expression, cellular distribution and enzyme activity of NKA following renal ischaemia-reperfusion (I-R) injury. The left renal pedicle of uninephrectomized female (F) and male (M) Wistar rats was clamped for 55 min followed by 2 h (T2) and 16 h (T16) of reperfusion. Uninephrectomized, sham-operated F and M rats served … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
38
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 38 publications
7
38
1
1
Order By: Relevance
“…Previously, we have shown that the I/R-induced translocation of the NKA ␣ 1 -subunit is less pronounced in F rats than in M. In parallel with this, the enzyme was also more active in F rats, which could possibly contribute to the gender differences in postischemic survival (14) and renal recovery (4).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Previously, we have shown that the I/R-induced translocation of the NKA ␣ 1 -subunit is less pronounced in F rats than in M. In parallel with this, the enzyme was also more active in F rats, which could possibly contribute to the gender differences in postischemic survival (14) and renal recovery (4).…”
Section: Discussionmentioning
confidence: 84%
“…Tubular damage and leukocyte infiltration were semiquantitatively evaluated on a scale [0, none (no necrotic tubules, no infiltrating cells); 1, mild (Ͻ25%, necrotic tubules, Ͻ10 cells); 2, moderate (26 -50% necrotic tubules, 11-50 cells); 3, massive (51-75% necrotic tubules, 51-100 cells); and 4, severe (Ͼ76% necrotic tubules, Ͼ101 cells)]. Nucleus atypia, vacuolization and hyalinization in the tubular cells, and dissolving, sloughing off, and lack of tubular cells such as hyaline in the tubules were used for more detailed quantification as described previously (4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies on acute renal injury have reported that females were relatively protected in comparison to males, have developed renal dysfunction in later periods of ischemic injury with lower BUN and creatinine levels, and had a lower mortality rate with a less severe tubular necrosis. [37][38][39] Despite the abundance of clinical and animal studies demonstrating that estrogens are renoprotective, the mechanisms by which estrogens exert their protective effects on the kidney remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%